Bagaimana Pengaruh Kualitas Pelayanan dapat Memberikan Kepuasan dan Loyalitas bagi Pelanggan di Restoran X Jakarta Selatan? - WULANDARI ASRI BASUKI (LPPM and Travel Operation Department Universitas Asa Indonesia, 2021)
ABSTRACT This study aims to analyze the effect of service quality on guest satisfaction and guest loyalty. The sample of this research is the customers of restaurant X totaling 120 respondents. Structural Equation Model (SEM) was used to analyze the data.) on guest satisfaction and guest loyalty. The sampling technique used is non-probability sampling, while the data analysis tool used is the SEM Structural Equation Modeling (SEM) analysis method as an alternative to the Partial Least Square (PLS) approach. The research method used in this research is quantitative analysis method using primary data such as observation and questionnaires. The results of this journal research indicate that each variable of intrinsic motivation, extrinsic motivation is a valid and reliable test result, some of which have a positive and significant effect on employee performance variables. Based on the results of data analysis and hypothesis testing with the results of each variable R Square value of 0.881 (88%) which means it has a very strong correlation to employee performance, and the rest is 0, 12 (12%) is influenced by other factors not examined the results of the R-Square value in the guest satisfaction variable (Y1), which is 0.888 with a percentage of 88%. This means that the results of the R-square value are very closely related to all indicators, or it can be explained that the influence of all indicators of physical evidence (X1), reliability (X2), responsiveness (X3), assurance and certainty (X4), appreciation/attention, perception (X5) gives a result of 0.888 which can be interpreted that the exogenous latent variable can be explained by the endogenous latent variable of 88% while 12% is explained by other variables outside the research journal. Keywords: Service Quality, Customer Satisfaction, Guest Loyalty